(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Employee motivation is a critical determinant of organizational success and long-term sustainability. This review explores the various dimensions of employee motivation, its underlying theories, and the impact it has on organizational performance. It synthesizes existing literature to highlight key motivational factors such as financial rewards, recognition, job security, career growth, and workplace relationships. The review further discusses the role of management practices and employee engagement in shaping motivation levels. Findings from multiple studies reveal that highly motivated employees contribute to enhanced productivity, job satisfaction, and reduced turnover rates. The article concludes by emphasizing the importance of adopting tailored motivational strategies that align with both organizational goals and employee expectations.